The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/fpsyg.2021.768962
|View full text |Cite
|
Sign up to set email alerts
|

Learning From Errors: Exploring the Effectiveness of Enhanced Error Messages in Learning to Program

Abstract: Error messages provided by the programming environments are often cryptic and confusing to learners. This study explored the effectiveness of enhanced programming error messages (EPEMs) in a Python-based introductory programming course. Participants were two groups of middle school students. The control group only received raw programming error messages (RPEMs) and had 35 students. The treatment group received EPEMs and had 33 students. During the class, students used an automated assessment tool called Mulber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The study suggests that students' competency in improving their code is important to their success in introductory programming. Also, in [19] authors explored the effectiveness of Enhanced Programming Error Messages (EPEMs) in a Python-based introductory programming course in the middle school using an automated assessment tool Mulberry.…”
Section: Related Workmentioning
confidence: 99%
“…The study suggests that students' competency in improving their code is important to their success in introductory programming. Also, in [19] authors explored the effectiveness of Enhanced Programming Error Messages (EPEMs) in a Python-based introductory programming course in the middle school using an automated assessment tool Mulberry.…”
Section: Related Workmentioning
confidence: 99%
“…Hattori and Kameda [32] and Becker et al [40,41] have developed tools for enhancing Java compiler error messages providing more information and changing description text for some common errors (through special front-end for the compiler), achieving good results. On the other hand, Zhou, et al [42] have not found the enhanced messages to be useful for help to reduce student errors or improve students' performance in debugging. Becker et al [43] present reliable evidence that this heuristic technique "fix the first error and ignore the rest" is trustworthy.…”
Section: Error Messages and Language Barriersmentioning
confidence: 99%
“…There is no need of modify compiler main program. Other challenging ideas include modify the compiler code for dealing with cascade error messages like presented by [40,41] and [32]; and, of course, enhancing error messages like done by [38,39,40,41,42].…”
Section: Didactic Features Project Ideas and Research Possibilitiesmentioning
confidence: 99%
“…However, it can help for recalling the programming concept and motivating their engagement. Learning from errors is another effective approach of making students learn in programming [4]. It helps students to understand the frequent errors they make while coding and the error messages from the compiler.…”
Section: Contributionmentioning
confidence: 99%